Upper critical field of NaFe1-xCoxAs superconductors - Ghannadzadeh, S; Wright, J; Foronda, F; Blundell, S; Clarke, S; Goddard, P (2014)
The upper critical field of NaFe1-xCoxAs was measured from x=0 to x=0.08, with the magnetic field applied parallel (Hc2â̂¥) and normal (Hc2âŠ¥) to the planes. The data were fitted using one-band and two-band models. The orbital and paramagnetic components of the upper critical field were extracted for Hc2â̂¥, which we find to be strongly dominated by paramagnetic pair breaking. In the parent compound the paramagnetic limit is equal to the value expected by BCS theory. However, substitution of Fe by Co leads to an enhancement above the BCS limit by a factor of approximately 1.6. In the overdoped region, we observe a significant convex curvature in Hc2âŠ¥ at low temperatures, which we attribute to the two-band nature of the superconductivity and the asymmetry between the two bands. Additionally, we discuss the behavior of critical field anisotropy, coherence length ξ, and the penetration depth λ. © 2014 American Physical Society.